POTATO YIELD EXPERIMENT IN TRIPOLI - ABDALLA, A.A. (The Libyan Journal of Agriculture, 2023)
1 - Yields of the majority of the cultivars were highest from the third sowing date ( 4-3-71 ). 2 - Radosa gave the highest yield in the first sowing date. It was one of the cultivars least infected with early blight in the first and second sowing dataa. 3 - Resy gave the highest yield in the second sowing date. It was also one of the cultivars least infected with early blight in the first and the second sowing dates. 4 - Spunta gave the highest yield in the third sowing date followed by Mary jice and Resy. 5 - Early blight was minimal in the third sowing date.